Hope at Workplace: A Review of the Literature - Mukherjee, Ujjal; Sharma, Pawan (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to understand the meaning of hope in different contexts and; develop an understanding on how hope influences different work related attitudes and behaviors.Key words such as origin of hope, psychological capital, consequences/antecedents of hope, importance of hope and; hope and organization were searched in Research Gate, Society for Human Resource Management (SHRM), American Physiological Association, Wiley Online Library, Indian Journals and Google Scholars to identify more than 100 articles. In- depth review was conducted to analyze the meaning, antecedents and consequences of hope in different contexts. The review has brought clarity in the definition and meaning of hope. The results suggest that, hope plays an important role in the overall wellbeing of an individual, especially at the workplace. Several research gaps have been identified for future researchers to pursue studies on hope. The article underlines the benefits of having hopeful employees in the organization.